MAIN DIRECTIONS AND RESULTS OF VEGETABLE BREEDING AND SEED PRODUCTION OF VEGETABLE CROPS OF LEGUMES IN VNIISSOK - V. F. Pivovarov; E. P. Pronina (Овощи России)
The paper demonstrates  the basic achievements in breeding and seed production  of vegetable  legumes  in All,Russian Research Institute  of vegetable  breeding  and seed production  and the directions  of the development  of advanced  varieties, which are very important at this stage.